S12.4 Genital warts: prevention, diagnosis, treatment and counselling. (10th July 2011) - Steben, M
Abstract : Genital warts (GW) are one of the most common reasons for consultation at an STI clinic. A majority of partners sexually exposed to GW will develop GW. Half of cases of GW will have cleared within 4 months. Condoms' efficacy has been demonstrated but need high compliance to achieve good protection. When lesions are not clearing reassessment of diagnosis may be necessary. Therapeutic options include patient applied and office base therapies. Some patients may need repeated cycles of therapy or combined modalities. Counselling for smoking cessation and HIV testing should be offered. High level of anxiety and sexual concerns are common. Partner notification is not recommended. Patients with GW and their actual and future partner(s) should be counselled about HPV quadrivalent prophylactic vaccine.